The Canadian Left: A Critical Analysis - Penner, Norman (Prentice-Hall, 1977)
When craftsman from Britain began to pour into Canada at the end of the nineteenth and the beginning of the twentieth century they brought more than industrial skills with them. They brought a trade union consciousness from a country where the labor movement was already highly developed, and many also came with socialist ideas, which they proceeded to implant on Canadian soil. Socialist ideas at the same time also came from the United States, and somewhat later immigrant laborers from eastern and central Europe added to the strength of socialism in Canada. –Introduction
Keywords: Socialism – Canada